MTHFR GENE POLYMORPHISM AMONG BHILS OF UDAIPUR, RAJASTHAN - Banerjee, Bhaswarupa; Saraswathy, Kallur Nava (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Methylenetetrahydrofolate reductase (MTHFR) ,an enzyme that in humans is encoded by the MTHFR gene, has a crucial role in regulating cellular methylation, through the conversion of 5,10- methyl-tetrahydrofolate(THF) to 5-methyl-THF, the methyle donor in the transformation of homocysteine to methionine. Reduced MTHFR activity due to the C677T change has been associated with different disorders, eg:, vascular disease, neural tube defects, Down’s syndrome and preeclampsia and spontaneous abortions. Moreover, many studies have showed the association of this polymorphism with the risk of colon, ovarian and breast cancer. The aim of the study is to screen MTHFR C677T single nucleotide polymorphisms among Bhils of Udaipur, Rajasthan and to compare our results with Indian and world populations. In present study a total number of 78 samples (both blood and buccal) were taken from randomly selected individuals (both males and females, unrelated upto first cousins). DNA extraction from samples was done by using High Yeild Genomic DNA extraction kit (Real Biotech Corporation) and Gentra Puregene Buccal Kit. Further using other molecular techniques like PCR-RFLP using Hinf I and gel electrophoresis. In the present study MTHFR gene is found to be polymorphic among the Bhils of Rajasthan with maximum number of CC (92.31%) genotype followed by CT (6.41%) and least by TT (1.28%) genotype. The population is not in the Hardy Weinberg Equilibrium with respect to the MTHFR polymorphism (P<0.05).